Outcome predictors in SARS-CoV-2 disease (COVID-19): The prominent role of IL-6 levels and an IL-6 gene polymorphism in a western Sicilian population. Issue 2 (August 2022) - Giannitrapani, Lydia; Augello, Giuseppa; Mirarchi, Luigi; Amodeo, Simona; Veronese, Nicola; Sasso, Bruna Lo; Giglio, Rosaria Vincenza; Licata, Anna; Barbagallo, Mario; Ciaccio, Marcello; Cervello, Melchiorre; Soresi, Maurizio
Highlights: Serum IL-6 levels predict COVID-19 disease severity and unfavorable outcomes. An IL-6 gene variant is a predictor of COVID-19 disease severity and unfavorable outcomes. Age and ischemic heart disease are important negative prognostic factors for COVID-19 disease.